ANALISIS KEPUASAN PASIEN BPJS TERHADAP PELAYANAN FARMASI PADA PESERTA PROGRAM RUJUK BALIK DI APOTEK KIMIA FARMA KARAWANG - Mochamad Fachri Saptayuda; Nia Yuniarsih; Lia Fikayuniar (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Pharmaceutical services in Indonesia that are required to change orientation from drug oriented to patient oriented. Pharmaceutical services are also carried out in one of the BPJS Health programs, namely the Referral Services Program (PRB). Referral service is a health service provided to patients in health facilities for referrals from specialist doctors or caring sub -specialists. Patient recovery is expected to be obtained from comfort, good pharmacy service, as well as from the drugs used by patients. Satisfaction is a feeling of happy or disappointed someone who is sourced from the impression of product performance (or results) is the same as his expectations. The result is high customer loyalty. The purpose of this study is to determine the level of satisfaction of pharmaceutical services at the Kimia Farma Karawang Pharmacy towards BPJS patients Referring Program. This research is a descriptive study with the cross sectional method and using prospective data. Data in the form of questionnaire sheets that have been filled out by respondents. The results obtained from this study are the level of satisfaction in the 65% tangible dimension, the level of satisfaction at the Reliability Dimension 52%, the satisfaction level in the responsiveness dimension of 65%, the level of satisfaction in the Assurance dimension 50%, and the level of satisfaction in the Empathy dimension 65%